2019
DOI: 10.1101/809400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matching cell lines with cancer type and subtype of origin via mutational, epigenomic and transcriptomic patterns

Abstract: 10

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Choosing the right cell line for specific experiments is key to getting the most reliable results. Therefore, a clear understanding of the context and properties of the selected cell line is critical for exploring biological mechanisms and predicting therapy response (19,20). Our previous study found that different porcine cell lines reveal differential susceptibility to SVV (13).…”
Section: Introductionmentioning
confidence: 99%
“…Choosing the right cell line for specific experiments is key to getting the most reliable results. Therefore, a clear understanding of the context and properties of the selected cell line is critical for exploring biological mechanisms and predicting therapy response (19,20). Our previous study found that different porcine cell lines reveal differential susceptibility to SVV (13).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Yu et al compared the transcriptomes of CCLs to The Cancer Genome Atlas (TCGA) by correlation analysis, resulting in a panel of CCLs recommended as most representative of 22 tumor types 15 . Most recently, Najgebauer et al 16 and Salvadores et al 17 have developed methods to assess CCLs using molecular traits such as copy number alterations (CNA), somatic mutations, DNA methylation and transcriptomics. While all of these studies have provided valuable information, they leave two major challenges unmet.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cell lines (64%) are assigned to clusters containing their specific cancer type though there is significant variation across cancer types with a median of 78% cell lines of a given cancer type showing concordance with the cancer type of its assigned cluster (Figure 3C). Prominent examples of divergence from expected cancer types include the cell lines FU97, NCI-H226, SW-1710 and JHH1, which have previously been associated with STAD, LUSC, BLCA and LIHC assigned as LIHC, MESO, KIRC/KIRP and UCEC respectively, an observation supported by other comprehensive approaches 60 . The cancer type with the most divergent assignments from expectation is LUAD.…”
Section: Resultsmentioning
confidence: 69%